2012
DOI: 10.4236/ajor.2012.23038
|View full text |Cite
|
Sign up to set email alerts
|

Almost Stochastic Dominance and Efficient Investment Sets

Abstract: A major drawback of Mean-Variance and Stochastic Dominance investment criteria is that they may fail to determine dominance even in situations when all "reasonable" decision-makers would clearly prefer one alternative over another. Levy and Leshno [1] suggest Almost Stochastic Dominance (ASD) as a remedy. This paper develops algorithms for deriving the ASD efficient sets. Empirical application reveals that the improvement to the efficient sets implied by ASD is substantial (64% reduction for FSD). Direct expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 26 publications
(30 reference statements)
0
3
0
Order By: Relevance
“…However, the relaxation of this assumption is conditional: The area of violation (i.e. the area where the cumulative probability distribution of B is above that of A) must be very small compared with the total area of the two distributions (Basu et al 2011;Levy 2009Levy , 2012. The SD decision-making criteria consider both risk and potential outcomes with the cumulative distribution function.…”
Section: Stochastic Dominance Decision-making Criteriamentioning
confidence: 99%
“…However, the relaxation of this assumption is conditional: The area of violation (i.e. the area where the cumulative probability distribution of B is above that of A) must be very small compared with the total area of the two distributions (Basu et al 2011;Levy 2009Levy , 2012. The SD decision-making criteria consider both risk and potential outcomes with the cumulative distribution function.…”
Section: Stochastic Dominance Decision-making Criteriamentioning
confidence: 99%
“…The budget is assumed not to be a constraint. The hybrid solution data are summarized in Table 7 and its cumulative distribution [41] and several of interest are depicted in Figure 3.…”
Section: Hybrid Solution Examplementioning
confidence: 99%
“…Some papers found that ASD rule can explain common practice in investments unanswered by SD rules (e.g., Bali et al, 2009;Levy, 2009;Bali et al, 2013) 3 . Moreover, researchers showed that investment efficient sets can be further improved by ASD rule (e.g., Levy, 2012).…”
Section: Introductionmentioning
confidence: 99%